2000
DOI: 10.1177/03635465000280051001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Calf Pain in Athletes Due to Sural Nerve Entrapment

Abstract: We retrospectively analyzed the charts of 13 athletes (18 limbs) who had sural nerve entrapment localized in the passage of the nerve through the superficial sural aponeurosis. There were 11 men and 2 women (average age, 43 years; range, 31 to 59). All patients reported chronic calf pain that was exacerbated during physical exertion. Delay to diagnosis averaged 9 months (range, 5 to 24). Tenderness in the calf was identified along the course of the sural nerve in all cases. In 10 patients (15 limbs) electrodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 7 publications
0
39
0
Order By: Relevance
“…SN entrapment was seen in one specimen. This abnormal course can produce pain upon contraction of the gastrocnemius muscle or altered sensation over the area of its distribution [19]. Many studies have reported SN entrapment [19][20][21][22].…”
Section: Other Findings Of Sural Nervementioning
confidence: 99%
“…SN entrapment was seen in one specimen. This abnormal course can produce pain upon contraction of the gastrocnemius muscle or altered sensation over the area of its distribution [19]. Many studies have reported SN entrapment [19][20][21][22].…”
Section: Other Findings Of Sural Nervementioning
confidence: 99%
“…Repetitive ankle inversion injuries may also lead to fibrosis and nerve entrapment. Sural nerve entrapment 66 can be an underdiagnosed cause of chronic calf and ankle pain, and it has been reported particularly in runners, soccer and tennis players [13].…”
Section: Sural Nervementioning
confidence: 99%
“…Sural nerve pathology is an uncommon diagnosis (Stickler et al, 2006), but is a condition that may be overlooked as differential diagnosis. For example, a retrospective analysis of 18 elite athletes with suspected chronic Achilles tendinopathy who failed conservative tendon management revealed that sural nerve entrapment was the cause of the symptoms (Fabre et al, 2000). Surgical release of the nerve resulted in positive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Entrapment of the nerve can be caused by compression due to fascial thickening, increased calf muscle mass, local scar tissue or mass-lesions, such as a benign or malignant tumour, haemorrhage or abscess (Fabre et al, 2000;Nicklas et al, 2006;Paraskevas et al, 2014). Ski boots, casts and tight footwear may increase pressure from externally (Brukner and Khan, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation